Examination of the Federal Capital Territory (FCT) Abuja Property Market Sub-Market - Abah, O. C.; Oladejo, I. E.; Egolum, C. C. (International Journal of Real Estate, 2025)
This study examines the structure, characteristics, and maturity of property sub-markets within the Federal Capital Territory (FCT), Abuja, Nigeria. Employing a survey research design, data were collected from 587 key stakeholders in the real estate sector, including estate surveyors, developers, financiers, and regulatory bodies. The research identifies the predominant property sub-markets, assesses their relative affordability, and evaluates the market’s responsiveness to investor needs. Findings reveal that the Abuja property market is largely dominated by residential (76.0%) and commercial (61.5%) sub-markets, while segments such as eco-friendly developments, tourism, and institutional properties remain underdeveloped. The study highlights significant affordability disparities among sub-markets, with government and institutional housing perceived as most accessible, and luxury and eco-friendly properties viewed as least affordable. The results indicate a partially mature market, characterized by professional depth, stable institutional presence, and increasing diversification. However, the limited participation in emerging sub-sectors underscores the need for policy-driven incentives to promote investment in underutilized segments. The study draws on the Market Cycle Theory to contextualize Abuja’s market dynamics and stresses the relevance of sub-market analysis in shaping urban development policy, housing strategies, and investment planning. It concludes by recommending diversification into underserved sub-markets, the adoption of green development practices, and supportive policies to enhance market inclusiveness and sustainability. These findings offer valuable insights for policymakers, investors, and planners aiming to harness the full potential of Abuja’s evolving property market.